Advances In Transition Metal Catalysis For Sustainable Chemical Processes (The Review of Diabetic Studies, 2025)
The advancement of green chemical manufacturing depends on the creation of sustainable catalytic systems. In contrast to commercial Pd/C catalysts, colloidal palladium nanoparticles supported on carbon (Pd/C) were synthesized in this study using a controlled colloidal route to increase activity, selectivity, and recyclability. In contrast to the heterogeneous particle sizes (7–18 nm) seen in conventional systems, transmission electron microscopy verified uniform nanoparticle dispersion with an average diameter of 3.8 ± 0.5 nm.In the Suzuki–Miyaura cross-coupling reaction, catalytic testing consistently produced high yields of 92–95.4%, while commercial Pd/C yielded 78.6% ± 3.1%. With selectivity above 95% and byproduct formation limited to ≤3%, the colloidal Pd/C demonstrated a turnover frequency (TOF) of 3,450 h⁻¹, a 68% increase over the reference catalyst. After five cycles, recycling tests showed that 85.7% of the initial activity was still present, while conventional Pd/C only retained 61.2%. Greater durability was highlighted by the colloidal system's low Pd leaching (0.8 ppm,